Breeding biology of the Magpie Goose - Johnsgard, Paul A (Wildfowl, 1961)
A breeding pair of Magpie Geese was studied at the Wildfowl Trust during one breeding season and part of a second. Nest-building was performed by both sexes and was done in the typical anatid fashion of passing material back over the shoulders. Nests were built on land of sticks and green vegetation. Two copulations were observed, both of which occurred on the nest, and precopulatory as well as postcopulatory behaviour appears to differ greatly from the typical anatid patterns. Eggs were laid at approximate day-and-a-half intervals, and the nest was guarded by both sexes. Incubation was also performed by both sexes, with the male normally sitting during the night. A simple nest-relief ceremony is present. The eggs hatched after 28 to 30 days, and the goslings left the nest the morning after hatching. Unlike all other Anatidae so far studied, the goslings, in addition to foraging independently, are fed directly by their parents and a special whistling begging call associated with a gaping posture is present. It is suggested that the bright bill colouration and unusual cinnamon-coloured heads of downy Magpie Geese are also related to this parental feeding. The parents constructed a ’brood nest’ of herbaceous vegetation that the goslings rested and slept on, which is also unique among the Anatidae. Family bonds are strong, and a rudimentary form of ’triumph ceremony’ is present. Development of the young and moulting sequences of downy, juvenal, and immature plumages are described; the presence of separate juvenal and immature plumages which are distinct from the adult plumage is apparently unique. It was also found that the juvenal rectrices are moulted shortly after fledging, which occurred on the 84th day, and the first remiges are moulted during the seventh and eighth months rather than at the end of the first year as is the usual anatid situation. A fully adult appearance, and presumably sexual maturity, is reached before the third year.